APPROXIMATION OF ( ψ, β )-DIFFERENTIABLE FUNCTIONS OF LOWSMOOTHNESS BY BIHARMONIC POISSON INTEGRALS - Kharkevych, Yurii I.; Zhyhallo, Kostiantyn M.; Харкевич, Юрій Іліодорович; Жигалло, Костянтин Миколайович (Ukrainian Mathematical Journal, 2012)
We solve the Kolmogorov–Nikol’skii problem for biharmonic Poisson integrals on the classes of ( ψ, β )-differentiable periodic functions of low smoothness in the uniform metric.